SKALA USAHA EKONOMIS PERHUTANAN SOSIAL Studi Komparasi pada Agroforestry dan Ekowisata di Yogyakarta dan Nusa Tenggara Barat - Yanto Rochmayanto; Fitri Nurfatriani; Andri Setiadi Kurniawan (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2019)
Farmers do not yet have extensive knowledge on the production economic. Therefore, the effectiveness of social forestry (SF) practices in providing economic benefits is still questionable. The study aimed to analyze the economic scale of SF as a lessons for the acceleration of land allocation of SF program. The study was focused on two schemes (community forestry and partnership), and two models of commodity (agroforestry and ecotourism). Study were located in six villages in DI Yogyakarta and East Nusa Tenggara. Data were collected through observation, in-depth interview, and documentation study. Economic scale was analyzed by break even point with profit contribution. The results showed that the economic scale on agroforestry was between 0.169.33 hectare, influenced by commodity preference especially multi purposes tree species. While economic scale for ecotourism was at least 542,897 visitors a year, and affected by number of ecotourism attraction. This study implies to provide policy recommendations: (1) ecotourism will be effective when it is conducted in the forest areas which have multi-attraction spots, and managed by community group with strong network, (2) the permit of timber harvesting within SF area must be easier and more open, and (3) the minimum area adjusted to the commodity as an important consideration for proposing SF.